Antibiotic resistance: A growing concern - Priyendu, Asim; Patel, Isha; Nagappa, Anantha Naik (Journal of Pharmacy Practice and Community Medicine)
The patterns of epidemics appear to have shifted from infectious diseases to lifestyle diseases. In the 20th century, antibiotics provided healthcare professionals a confidence that no infectious diseases can be a serious threat to individuals or the population. Eventually, the resistant infectious diseases replaced the conventional bacteria.[1] The advent of Methicillin resistant Staphylococcus aureus, NDM1E.coli, VRE, Klebsiella pneumonia, etc. better known as “Superbugs” showed extended resistance to conventional antibiotics.[2,3] In India, many people develop resistance to antibiotics. Excessive use of antibiotics leads to mutations in bacteria, which are essentially adaptations to overcome the assault of the chemotherapeutic agents. The irrational use of antibiotics is difficult to control. For example, the antibiotics used in the hospitals for treating patients are likely to enter the sewage system of hospitals which may serve as a source of resistant organisms. The indiscriminate use of antibiotics for self-medication by procuring them over the counter is another reason for antibiotic resistance leading to irrational use of antibiotics although a potential threat difficult to ban and prevent. Similarly, many antibiotics are used in subtherapeutic doses leading to bacterial resistance.